"You better use the safer one... leave this one": the role of health providers in women's pursuit of their preferred family planning methods - Robel Yirgu; Shannon N. Wood; Celia Karp; Amy Tsui; Caroline Moreau (BMC, 2020)
Abstract Background Universal access to quality sexual and reproductive health (SRH) services is pivotal to ensuring gender equality. In high-income countries, patient-provider interactions have been shown to shape women's decisions about contraception, with poor exchanges decreasing method uptake and satisfaction. While significant progress has been made to increase women's access to SRH services, in low- and middle-income countries, little is known about the quality of family planning patient-provider interactions. The primary objective of this analysis was to explore the role of health care providers in women's family planning decision-making in Ethiopia. Methods From July to August 2017, 10 focus group discussions (n = 80) and 30 in-depth interviews were conducted with women aged 15-49 and men aged 18+ recruited via purposive sampling from urban and rural sites in Ethiopia. Semi-structured interview guides explored women's and girls' empowerment in SRH surrounding sex, childbearing, and contraception. All interviews were conducted in Amharic, audio-recorded, and transcribed verbatim into English. Inductive thematic analysis was used to analyze data. Eleven codes specific to provider services for family planning were reviewed and matrixes creates for synthesis. Results Three primary themes emerged: the role of providers in women's awareness of and demand for family planning services; selection and uptake of contraceptive methods; and discontinuation and switching of contraceptive methods. Results indicate that health extension workers were central to women's awareness of family planning, and health providers' endorsements were instrumental in decisions to adopt methods. The majority of respondents described positive interactions with providers and appreciated thorough counseling when considering using or switching methods. Some women, however, described health providers directing them toward long-acting methods by communicating inaccurate information or emphasizing disadvantages of short-acting methods. A few women described provider reluctance or resistance to switching methods, especially from implants. Conclusions Women shared many narratives about the central roles health providers played in their awareness and decision-making for family planning. Those narratives also included provider bias against women's preferred methods. Further research and program assessments are needed to ascertain the extent to which these biases hinder women's decision-making autonomy in using contraception.